2010
DOI: 10.1111/j.1600-051x.2010.01590.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an individually tailored oral health educational programme on periodontal health

Abstract: ITOHEP intervention in combination with scaling is preferable to the ST programme in non-surgical periodontal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
153
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(169 citation statements)
references
References 27 publications
6
153
0
2
Order By: Relevance
“…A recent study found periodontal health improvements in plaque, calculus, and gingivitis indexes after an average of three sessions of education and professional care among the elderly, mental patients, and patients hospitalized in an intensive care unit 20,21 . Another recent effort toward behavior change and periodontal health promotion in the form of a personalized education program targeted adults older than 20 years 22,23 .…”
mentioning
confidence: 99%
“…A recent study found periodontal health improvements in plaque, calculus, and gingivitis indexes after an average of three sessions of education and professional care among the elderly, mental patients, and patients hospitalized in an intensive care unit 20,21 . Another recent effort toward behavior change and periodontal health promotion in the form of a personalized education program targeted adults older than 20 years 22,23 .…”
mentioning
confidence: 99%
“…Most studies conducted to date in dentistry, using the MI technique, were held in dental schools, according to methodological models that evaluated the effectiveness of interventions [2,5,10]. However, it is necessary that intervention results conducted under ideal conditions are tested in services and in populations with different socioeconomic and cultural levels, in order to provide effective ways of incorporating these technologies into practical services.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the promising results [9], most studies that used the MI technique in dentistry and in patients with periodontal problems was developed in the USA and Europe, and applied to individuals who sought care in dental schools clinics [2,5,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…10,13 The results of recent studies suggest that individualized and patientcentered educational interventions, based on health behavior theories, are preferable to conventional educational interventions in order to improve the patient's adherence to self-performed periodontal infection control. 8,14,15 Educational intervention programmes directed to patients in treatment for chronic periodontitis have traditionally been given "step by step," including (i) detailed information through pamphlets about signs and symptoms of the disease and their relationship to the presence of bacterial biofilms and the patients' periodontal status, (ii) demonstration of the presence of signs, symptoms and locations of the disease in the patient's mouth, (iii) detailed information about the importance of efficient daily oral hygiene followed by oral hygiene instructions, and (iv) the use of disclosing solution for plaque staining as a pedagogical tool to demonstrate where the bacterial plaque is located. Adherence with the information provided and the patient's oral hygiene status are then monitored at subsequent treatment sessions 16 Yet, motivating patients to change their oral health behavior is indeed a challenge for dental professionals and a complex issue, which has led to the introduction of Motivational Interviewing (MI) in dentistry .…”
Section: Health Education Interventionsmentioning
confidence: 99%